Mild two-step conversion of primary amides to alcohols by reduction of acylimidodicarbonates with sodium borohydride - Ragnarsson, Ulf (2003)
Di-tert-butyl acylimidodicarbonates, prepared from primary amides with two equivalents of di-tert-butyl dicarbonate under catalysis by 4-dimethylaminopyridine, readily undergo selective reductive cleavage of their acyl CO-N bonds by NaBH4 to provide the corresponding alcohols in high yields.